1979
DOI: 10.1093/ajcn/32.12.2400
|View full text |Cite
|
Sign up to set email alerts
|

Estimating fat body mass from anthropometric data

Abstract: Regression equations have been derived for the calculation of fat body mass in boys from 4 to 12 1/2 years old and girls 4 to 19 years old. Height and weight give a good prediction of fat body mass, but the addition of skinfold thicknesses to the regression equations reduces the number of large errors in the estimates. The regression equations and the limits of accuracy are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The com-position of fatty acids in cirrhotic patients resembles that found in situations of linoleic acid deficiency (24)(25)(26)(27). It is known that patients with hepatobiliary disease suffer frequently from an anorexic, emetic and nauseous state, which in chronic situation can lead to severe malnutrition (28). In fact, the anthropometric estimation (29) of the two cirrhotic subgroups (data not shown) indicated that 50% of the uncompensated were clearly undernourished, while the rest were poorly nourished.…”
Section: Discussionmentioning
confidence: 94%
“…The com-position of fatty acids in cirrhotic patients resembles that found in situations of linoleic acid deficiency (24)(25)(26)(27). It is known that patients with hepatobiliary disease suffer frequently from an anorexic, emetic and nauseous state, which in chronic situation can lead to severe malnutrition (28). In fact, the anthropometric estimation (29) of the two cirrhotic subgroups (data not shown) indicated that 50% of the uncompensated were clearly undernourished, while the rest were poorly nourished.…”
Section: Discussionmentioning
confidence: 94%
“…Weight-for-height and height-for-age Z scores were calculated in relation to the median of the NCHS reference population [2] and Total energy expenditure by the doubly-labeled water method in rural preschool children in Cuba the Cuban reference data [3,4]. Fat mass and fat-freemass were estimated using Dugdale and Griffiths´s equation [5].…”
Section: Anthropometrymentioning
confidence: 99%
“…Horm Res I997;48(suppl l): [33][34][35][36][37][38][39][40][41][42] tions that combine several skinfold thickness measure ments and/or other measurements also combine their measurement errors.…”
Section: K1gs: Body Composition In Childrenmentioning
confidence: 99%